Qualitative Content Analysis of Soft-Selling Marketing Messages in The Short Film “Pulang” - Arief Oscar Navero; Nicholas Pranata (IMAJI, 2026)
In the post-pandemic era, public utilities and transportation services have faced challenges in rebuilding customer trust. PT Kereta Api Indonesia (Persero) addressed this by creating a branded short film, "Pulang" (2023), for its digital marketing and Eid homecoming initiative. This research identifies and analyzes how implicit soft-selling marketing messages are integrated into the film's storytelling and cinematography. Using a descriptive qualitative method and content analysis, 22 key scenes were examined across six aspects: station setting, corporate services, physical features, digital application usage, train amenities, and ambiance. Findings reveal that PT KAI utilized a branded entertainment strategy, featuring mostly soft-selling techniques, with 21 scenes focused on this approach and only 1 scene using hard-selling. The film incorporates heartwarming family reunion themes and appealing visuals, promoting "narrative transportation" to enhance brand memory and reduce ad resistance. This study highlights how public utility organizations can leverage cinematic storytelling as a non-intrusive marketing strategy.